MOLECULAR DETECTION OF INSERTION SEQUENCE 6110 OF MYCOBACTERIUM TUBERCULOSIS IN PATIENTS WITH PULMONARY TUBERCULOSIS AND TUBERCULOUS PLEURITIS IN ANBAR GOVERNORATE, WEST OF IRAQ: Life Sciences-Microbiology - DR. MUSHTAK T.S. AL-OUQAILI (International Journal of Life Science and Pharma Research, 2022)
Accurate identification and early diagnosis of tuberculosis especially latent and active infection is the key to prevention of the disease. This study was conducted to detect the accuracy of conventional and real time polymerase chain reaction in the diagnosis of pulmonary tuberculosis caused by Mycobacterium tuberculosis in sputum and blood samples using 123 bp gene of repetitive insertion sequence 6110 (IS6110) of bacterial genome and tuberculous pleuritis using pleural effusion. Sixty five patients who have clinical suspicion of pulmonary tuberculosis, fifty patients with suspicion of TB pleurisy and twenty patients with non-tuberculous mycobacterial pulmonary disease as control were studied during the period from April, 2012 to December, 2015. They were admitted to Department of Internal Medicine in Ramadi Teaching Hospital and Clinical Private. EDTA-Peripheral blood and sputum samples had been taken from patient with pulmonary tuberculosis. Also, pleural effusion was obtained from patients with tuberculous pleuritis. They were subjected to DNA extraction, amplification of the target DNA by conventional PCR and qualitative real time PCR. Of the 65 sputum samples from patients with pulmonary tuberculosis, 37 (56.9%) were AFB smear-positive. Of these, 32 (86.5%) and ?? (94.6%) were positive for PCR and RTPCR respectively. Further, out of 28 negative smear, 7 (25%) and 8 (28.6%) smears were PCR and RTPCR positive respectively. Further, in peripheral blood based PCR study, out of 37 patients whose sputum were positive by AFB smear, only 25 (67.6%) of them were positive for PCR. Peripheral blood based PCR and RT-PCR essays were negative for all AFB smear negative cases. In suspected tuberculous pleuritis, 8 (16%), 9 (18%) patients reveal positive result for both of conventional and real time PCR respectively. Also, all twenty spontaneous sputum samples (controls)were negative for PCR. The study concluded that PCR provides a sensitive and specific means for laboratory diagnosis of pulmonary tuberculosis and qualitative real time PCR is a more confirmatory test but the molecular diagnosis of the tuberculosis should be based on the combined analysis of baciloscopia, clinical manifestations and therapeutic proves. Further, it was concluded that PCR and RT-PCR based- peripheral blood leukocytes is of little value for specific diagnosis of pulmonary tuberculosis. Regarding tuberculous pleuritis, PCR test revealed low sensitivity and high specificity using pleural fluid. The sensitivity was higher in cases in which the bacillary load was high-in acid fast bacilli-positive samples.